2001: tricentenaire de la Grande Paix de Montréal - Beaudoin, Léo (Montréal en tête, 2001)
issued: 2001-24-00
Keywords: Autochtones; Français; Grande Paix de Montréal; Guerre; Iroquois

Le tricentenaire de la Grande Paix de Montréal. Montréal, juillet-août 1701 - Beaudoin, Léo (Montréal en tête, 2001)
issued: 2001-21-00
Keywords: Autochtones; Callière; Louis-Hector de; Fortifications; Fourrure; Gouverneurs; Grande Paix de Montréal; Guerre

1920-2001, 81 ans de solidarité ouvrière - Fournier, Roseline; Houle, Louis-Serge (Conseil central du Montréal métropolitain, CSN, 2001)
Keywords: Confédération des syndicats nationaux; Conseil central des syndicats nationaux de Montréal

La réorganisation du travail à la raffinerie Shell de Montréal-Est, de 1989 à 1999 - Delorme, Marie-Josée (Université de Montréal, 2001)
Keywords: Montréal-Est; Pétrole; Travail

The Great Peace of Montreal of 1701: French-Native Diplomacy in the Seventeenth Century - Havard, Gilles (McGill-Queen's University Press, 2001)
Translators: _:n12897
Keywords: Autochtones; Français; Grande Paix de Montréal

From the Ghetto to the Main: the Story of the Jews of Montreal - King, Joe (Montreal Jewish Publications Society, 2001)
Keywords: Juifs

La Grande Paix: chronique d'une saga diplomatique - Beaulieu, Alain; Viau, Roland (Libre Expression et Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 2001)
Keywords: Autochtones; Français; Grande Paix de Montréal; Iroquois

Le transport à vélo: le cas des étudiants de l'Université du Québec à Montréal - Moran, Anne-Marie (Université du Québec à Montréal, 2001)
Keywords: Cyclisme; Université du Québec à Montréal; Étudiants

Pectus est quod disertos facit: éloquence et sublime dans la Rhétorique (1796) de Jacques-Antoine Houdet - Bélanger, Anne; Landry, Alexandre (Archives et fabrique du textile littéraire, 2001)
Keywords: Collège de Montréal; Communautés religieuses; Sulpiciens

La Faculté de théologie de l'Université de Montréal: mémoire et histoire, 1967-1997 - Sauvé, Madeleine (Fides, 2001)
Keywords: Théologie; Université de Montréal

The Great Peace of Montreal, 1701 - Matusky Gedeon, Julia (The Beaver, 2001)
issued: 2001-06/2001-07
Keywords: Autochtones; Français; Grande Paix de Montréal

Jules Gilbert: pionnier de l'éducation sanitaire - Gaumer, Benoît; Desrosiers, Georges (Lidec, 2001)
Keywords: Médecine; Université de Montréal

Les lieux de la paix de 1701, et autres considérations sur les campements amérindiens à Montréal - Johnson, Laurence (Recherches amérindiennes au Québec, 2001)
Number: 2
Keywords: Autochtones; Français; Grande Paix de Montréal

Les signatures amérindiennes: essai d’interprétation des traités de paix de Montréal de 1700 et de 1701 - Guillaud, Yann; Delâge, Denis; D'avignon, Mathieu (Recherches amérindiennes au Québec, 2001)
Number: 2
Keywords: Autochtones; Français; Grande Paix de Montréal

The Great Peace: Chronicle of a Diplomatic Saga - Beaulieu, Alain; Viau, Roland (Libre Expression, 2001)
Translators: _:n12489
Keywords: Autochtones; Français; Grande Paix de Montréal

The Protestant Orphan Asylum and the Montreal Ladies' Benevolent Society: A Case Study in Protestant Child Charity in Montreal, 1822-1900 - Harvey, Janice (Université McGill, 2001)
Keywords: Enfants; Famille; Femmes; Montreal Ladies' Benevolent Society; Protestants

Analyse de l'engagement organisationnel de professionnels œuvrant dans une institution universitaire québécoise - Côté, Ghislaine (Université du Québec à Montréal, 2001)
Keywords: Université du Québec à Montréal

Histoire des écoles d'Hochelaga-Maisonneuve. Tome 1. L'École Notre-Dame-de-l'Assomption (Louis-Jolliet) - Cadotte, Robert; Noël, Colette (Commission scolaire de Montréal et Atelier d'histoire Hochelaga-Maisonneuve, 2001)
Keywords: Hochelaga (quartier); Maisonneuve; Quartiers

Perceptions linguistiques à Montréal - Laur, Elke (Université de Montréal, 2001)
Keywords: Langue

Memory and Migration: Ethiopian Jews in Montreal - Djerrahian, Gabrielle (Université de Montréal, 2001)
Keywords: Africains; Juifs

Plus que parfaites: les aides familiales à Montréal, 1850-2000 - Groot, Raphaëlle de; Ouellet, Élizabeth (Remue-ménage, 2001)
Keywords: Domestiques; Femmes; Institut du Bon-Conseil

Transmission culturelle aux enfants par de jeunes couples immigrants. Montréal, Québec, Sherbrooke - Helly, Denise; Vatz-Laaroussi, Michèle; Rachedi, Lilyane (Immigration et Métropoles, 2001)
Keywords: Enfants

The Historical Record and Adolescent Girls in Montreal’s Red-Light District - Myers, Tamara (Framing Our Past: Constructing Canadian Women’s History in the Twentieth Century, 2001)
Keywords: Enfants; Femmes; Prostitution

Jeunes filles affiliées aux gangs de rue à Montréal: cheminements et expériences - Fournier, Michèle (Université de Montréal, 2001)
Keywords: Criminalité; Délinquance

Le mouvement communautaire haïtien de Montréal en tant que mouvement social - Boucard, Alix (Université de Montréal, 2001)
Keywords: Haïtiens

L'identité ethnolinguistique de jeunes adultes issus de couples mixtes francophones/anglophones à Montréal - Hadiri, Myriam (Université de Montréal, 2001)
Keywords: Anglophones; Francophones; Langue

Le monde social de la rue: expériences des jeunes et pratiques d'intervention à Montréal - Bellot, Céline (Université de Montréal, 2001)
Keywords: Itinérance

Le jeûne du ramadan en contexte de migration: le cas des immigrants d'origine marocaine à Montréal - Grégoire, Anne-Josée (Université de Montréal, 2001)
Keywords: Maghrébins; Marocains

"Identification des valeurs, des objectifs et des finalités actuels et souhaités de l'éducation chez les musulmans de la région de Montréal" - Aoui, Jamel (Université de Montréal, 2001)
Keywords: Musulmans

Le suicide dans le district judiciaire de Montréal (de 1815 à 1843 et de 1893 à 1903) - Bordeleau, François (Université du Québec à Montréal, 2001)
Keywords: Mortalité

Parcours d’une collaboration: les intervenants psychiatriques et psychologiques à la Cour des jeunes délinquants de Montréal (1912-1950) - Quevillon, Lucie (Université du Québec à Montréal, 2001)
Keywords: Délinquance; Enfants; Psychologie; Tribunaux

Du képi au kippa: implantation des nouvelles politiques de rapprochement du service de police de la Communauté urbaine de Montréal en milieu hassidique - Shamlian, Isabelle (Université du Québec à Montréal, 2001)
Keywords: Hassidim; Juifs; Police

Le comportement de consommation artistique et culturel des groupes ethniques à Montréal: le cas des Français, des Vietnamiens, des Libanais et des Haïtiens - Ndiaye, Sophie (Université du Québec à Montréal, 2001)
Keywords: Français; Haïtiens; Libanais; Vietnamiens

L'expérience de la pratique de la danse salsa des jeunes adultes dans deux discothèques latines de Montréal: une participation à une culture, une rencontre, un rituel - Burelle, Édith (Université du Québec à Montréal, 2001)
Keywords: Danse; Latino-Américains

Les pratiques de gestion dans les PME de la communauté haïtienne de Montréal - Michel, Dicarmel (École des hautes études commerciales de Montréal, 2001)
Keywords: Haïtiens

La dynamique sociale entourant les jardins communautaires: l'individu, le groupe et le jardin. Le cas de Montréal - Daclon Bouvier, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Groupes populaires; Jardins

Manly Smokes: Tobacco Consumption and the Construction of Identities in Industrial Montreal, 1888-1914 - Rudy, Robert Jarrett (Université McGill, 2001)
This dissertation explores the cultural practice of smoking and its connection to social relations from the beginning of cigarette mass production in Montreal in 1888 to the First World War. It uncovers the norms of smoking etiquette and taste, their roots in gender, class and race relations and their use in reproducing these power relationships. It argues that these prescriptions reflected and served to legitimize beliefs about inclusion, exclusion and hierarchy that were at the core of nineteenth century liberalism. Liberal ideals of self-control and rationality structured the ritual of smoking: from the purchase of tobacco; to who was to smoke; to how one was supposed to smoke; to where one smoked. These prescriptions served to normalize the exclusion of women from the definition of the liberal individual and to justify the subordination of the poor and cultural minorities. Furthermore, even while these prescriptions were at their height, an emergent group of beliefs began to recast notions of respectable smoking around new ideals of speed and ungendered universality. This challenge was not only part of the transition from bourgeois to mass consumption, it was the roots of a transformation of the liberal order in the years previous to the First World War.
Keywords: Tabac

Toot Sweet: When Jazz Ruled Montreal - Reynolds, Mark (The Beaver, 2001)
issued: 2001-06/2001-07
Keywords: Musique; Noirs

Ces médecins montréalais en marge de l'orthodoxie - Desjardins, Rita (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2001)
Number: 2
Keywords: Médecine

Intégration et transnationalisme chez les Dominicains de Montréal - Dancause, Jacques-Luc (Université McGill, 2001)
Keywords: Caribéens

Le Black Theatre Workshop de Montréal: un nouveau bilan - Bayne, Clarence (L'annuaire théâtral, 2001)
issued: 2001-21-00
Keywords: Noirs; Théâtre

The Feminization of Clerical Work in Early Twentieth-Century Montreal - Boyer, Laura Kate (Université McGill, 2001)
Keywords: Femmes; Travail

Political Economy, Transnationalism, and Identity: Students at the Montreal Hoshuko - Yoshida, Reiko (Université McGill, 2001)
Keywords: Japonais; Nationalisme

Plus que parfaites: un siècle de services domestiques à Montréal - Bourbeau, Amélie (Cap-aux-Diamants, 2001)
issued: 2001-22-00
Keywords: Domestiques; Femmes

La contestation des espaces gais au centre-ville de Montréal depuis 1950 - Guindon, Jocelyn M. (Université McGill, 2001)
Keywords: Police; Quartiers

Deserting Daughters: Runaways and the Red Light District of Montreal before 1945 - Myers, Tamara (Child Welfare and Social Action: Nineteenth and Twentieth Centuries, 2001)
Keywords: Délinquance

Le Montréal juif entre les deux guerres / Tsvishn tsvey velt milhomes - Medresh, Israël (Septentrion, 2001)
Translators: _:n32043
Keywords: Juifs

Under Reconstruction: the Family and the Public in Postwar Montréal, 1944-1949 - Fahrni, Magda (Université York, 2001)
Keywords: Famille; Guerre

Groupes, identités et municipalités dans l’histoire de Montréal et de sa région - Linteau, Paul-André (Ministère des Affaires municipales et de la Métropole du Québec, 2001)

La dépression politique des Anglo-Montréalais lors de la crise des années trente - Jedwab, Jack (Bulletin d'histoire politique, 2001)
issued: 2001-24-00
Keywords: Anglophones; Crise

The Identification of Employment Centres in Canadian Metropolitan Areas: the Example of Montreal, 1996 - Coffey, William J.; Shearmur, Richard (The Canadian Geographer / Le Géographe canadien, 2001)
Number: 3

‘Preach the World’: Canadian Imperialism and Missionary Outreach at the Montreal Diocesan Theological College, 1892-1903 - Mills, Sean (Journal of the Canadian Church Historical Society, 2001)
issued: 2001-21-00
Keywords: Anglicans; Missions; Protestants; Théologie

La ville, miroir et enjeu de la santé: Paris, Montréal et Alger au XXe siècle - Goubert, Jean-Pierre (Histoire, économie et société, 2001)
issued: 2001-07/2001-09
Keywords: Vaccination; Épidémies

"A Most Detestable Crime": Gender Identities and Sexual Violence in the District of Montreal, 1803-1843 - Ramos, Sandy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Number: 1
Keywords: Femmes

HIV Risk Behaviour and Predictors of Initiation into Prostitution among Female Street Youth in Montreal, Canada - Weber, Amy E. (Université McGill, 2001)

La paroisse urbaine comme communauté sociale: l'exemple de Saint-Pierre-Apôtre de Montréal, 1848-1930 - Ferretti, Lucia (La paroisse, 2001)
Keywords: Communautés religieuses; Oblats de Marie-Immaculée; Saint-Pierre-Apôtre (paroisse)

“Le Québec a charge d’âme”: l’Action française de Montréal et les minorités françaises (1917-1928) - Bock, Michel (Revue d'histoire de l'Amérique française, 2001)
En s'appuyant sur l'exemple de la revue mensuelle L'Action française, cet article cherche à circonscrire la place des minorités françaises du Canada dans le nationalisme canadien-français des années 1920, problématique négligée par les historiens. L'auteur démontre que la conception « romantique » qu'avait la revue de la nation canadienne-française faisait des minorités les vestiges ou le prolongement du grand « Empire français d'Amérique », argument qui sera fréquemment utilisé par la rédaction afin de revendiquer le respect de leurs droits scolaires et religieux. Par ailleurs, ce n'est que lorsque considérés en fonction des minorités françaises que quelques-uns des plus importants thèmes du nationalisme canadien-français, comme la mission providentielle du Canada français, trouvent tout leur sens. La nation étant une entité « organique », L'Action française assignait également au Québec un devoir de solidarité nationale envers les minorités aux prises avec les politiquesassimilatrices de la majorité anglo-protestante du pays.
issued: 2001-24-00
Keywords: Action française (L'); Nationalisme

Dealing with "the Destitute and the Wretched": The Protestant House of Industry and Refuge in Nineteenth-Century Montreal - Harvey, Janice (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
Number: 1
Keywords: Itinérance; Philanthropie; Protestants

Vive la Canadienne! Les représentations de l’identité féminine dans le défilé de la Saint-Jean-Baptiste à Montréal (1924-1961) - Demers, Michel (Université de Sherbrooke, 2001)
Keywords: Femmes; Saint-Jean-Baptiste (fête)

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

The Practice and Meaning of Bonsai, Ikebana, and Tea in Montreal and Abroad: A Case Study of the Processes of Cultural Globalization - Wilson, Hayley (Université Concordia, 2001)
Keywords: Japonais

L'éducation "idéale" dans un monde "idéal": le Dunham Ladies' College / St. Helen's School et l'élite anglicane du diocèse de Montréal (1870-1930) - Harbec, Marie-Ève (Université McGill, 2001)
Keywords: Anglicans

La FTQ, ses syndicats et la société québécoise - Bélanger, Yves; Comeau, Robert; Métivier, Céline (Comeau & Nadeau, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

La FTQ et le Québec syndical - Clément, Carole; Fédération des travailleurs et travailleuses du Québec (Fédération des travailleurs et travailleuses du Québec, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

Analyse comparative des politiques et interventions en habitation - Dansereau, Francine; Divay, Gérard; Rose, Damaris; Sénécal, Gilles; Séguin, Anne-Marie; Aubrée, Loïc (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2001)
Keywords: Logement

Analyse comparative des politiques de logement en regard des problématiques et tendances récentes - Dansereau, Francine; Divay, Gérard; Aubrée, Loïc; Rose, Damaris; Sénécal, Gilles; Séguin, Anne-Marie (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2001)
Keywords: Logement

Gustave Francq: figure marquante du syndicalisme et précurseur de la FTQ - Leroux, Éric (VLB, 2001)
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

La pensée de Gustave Francq, syndicaliste et réformateur social: textes choisis, 1905-1948 - Francq, Gustave; Leroux, Éric (Regroupement des chercheurs-chercheures en histoire des travailleurs et travailleuses du Québec, 2001)

Chiniquy - Trudel, Marcel (Lidec, 2001)
Keywords: Chiniquy; Charles

Mother Marie-Rose: Eulalie Durocher, 1811-1849 - Laberge, Yolande (Lidec, 2001)
Translators: _:n48594
Keywords: Communautés religieuses; Durocher; Eulalie; Soeurs des Saints Noms de Jésus et de Marie

Jardins d'un autre temps. Deux jardins dans l'esprit de la Nouvelle-France - Tairraz, Monique (Maison Saint-Gabriel et Musée du Château Ramezay, 2001)
Keywords: Alimentation; Jardins; Maison Saint-Gabriel; Ramezay (château de)

Guido Nincheri artiste entrepreneur - Laroche, Ginette (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Peinture; Vitraux; Églises

Guido Nincheri muraliste - Laroche, Ginette; Pellissier, Pierlucio (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Peinture; Églises

Le vitrail au studio de Guido Nincheri - Laroche, Ginette (Guido Nincheri: un artiste florentin en Amérique, 2001)
Keywords: Arts sacrés; Vitraux; Églises

Analyse des valeurs patrimoniales du site et des bâtiments de l'Oratoire Saint-Joseph du Mont-Royal - Tanguay, Caroline (2001)
Keywords: Oratoire Saint-Joseph; Patrimoine

Les trajectoires des jeunes d'origine haïtienne dans le système québécois de protection de la jeunesse - Bernard, Léonel (Université de Montréal, 2001)
Keywords: Haïtiens

Appréhender la nation, vivre la diaspora regards arméniens - Lenoir-Achdjian, Annick (Université de Montréal, 2001)
Keywords: Arméniens

Daniel Coussirat (1841-1907): la vie et l’œuvre d’un intellectuel franco-protestant - Hamelin, Charles (Université de Montréal, 2001)
Keywords: Protestants

Libéralisme, nationalisme et catholicisme dans la pensée politique de Claude Ryan au Devoir (1962-1978) - Marcil, Olivier (Université de Montréal, 2001)
Keywords: Devoir (Le); Idéologies; Libéralisme; Nationalisme; Ryan; Claude

Le théâtre d'intervention et les jeunes de la rue - Dagenais, Bernard (Université du Québec à Montréal, 2001)
Keywords: Itinérance; Théâtre

L'évaluation d'une intervention: le travail de rue dans un organisme communautaire PACT de rue - Allaoui, Saandiya (Université du Québec à Montréal, 2001)
Keywords: Itinérance

L'apport des services de proximité en matière de revitalisation socio-économique des quartiers - Rochefort, Michel (Université du Québec à Montréal, 2001)
Keywords: Quartiers

Tibetans in Québec: Proﬁle of a Buddhist Community - Cormier, Louis (Université du Québec à Montréal, 2001)
Keywords: Tibétains

Pratiques et stratégies spatiales des employées de bureau montréalaises dans un contexte de décentralisation économique - Chicoine, Nathalie (Institut national de la recherche scientifique et Université du Québec à Montréal, 2001)
Keywords: Femmes; Travail

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens